Effect of riparian vegetation on the spatial distribution of slimy sculpin cottus cognatus in southwestern Wisconsin streams - Laukkanen, Katri Helena (My University, 2012)
The distribution of freshwater sculpin (Coitus spp.), are frequently associated with the quantity and quality ofmacroinvertebrate prey, which are often influenced by the presence of riparian vegetation. I hypothesized that open- canopies would increase primary and secondary production in riffles, and would result in greater densities of slimy sculpin (Cottus cognatus) than in riffles underlying closed- canopies. The quantity of periphyton and macroinvertebrates, and the density and size-frequency distribution of slimy sculpin were monitored for three months in riffles with open- and closed- canopy in three streams in the Coon Creek watershed, Wisconsin. Sculpin densities were not significantly different between riffles with open- or closed- canopies, nor were there differences in periphyton and macroinvertebrate standing crop. However, the sizefrequency distribution of sculpin varied by canopy type; a larger proportion of juvenile and small-bodied sculpin were collected in riffles with open- canopies than in riffles with closed- canopies. Many juvenile sculpin were sampled from within macrophyte beds growing in open- canopy riffles. These results suggest that the quantity of photosynthetically active radiation may not influence the density of sculpins through enhancement of periphyton and subsequent increases in macroinvertebrate prey, but rather, may influence the size distribution of sculpin by increasing the growth of macrophytes, which serve as an important habitat for juvenile slimy sculpin.
Keywords: Microorganisms; Riparian plants, Wisconsin